1985
DOI: 10.2307/3899336
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Physical Attributes of Seeds of Some Common Sagebrush-Steppe Plants: Some Implications for Ecological Theory and Management

Abstract: A study was conducted to identify seed attributes which might influence granivore preferences. Physical and chemical characteristics were estimated for seeds of 7 common sagebrush-steppe species (Artemisia tridentata, Bromus tectorum, Oryzopsis hymenoides, Pascopyrum smithii, Purshia tridentata, Stipa comata and Stipa viriduia) and 1 sacrifice food species (Panicum miliaceum). Seed-weights and caloric contents were determined, as well as % composition contributed by 5 organic, 3 inorganic and 5 synthetically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…A simple explanation for the strong preference for Indian ricegrass exhibited by kangaroo rats in this and numerous other studies (Kelrick and MacMahon ; Longland et al. ; Veech ) is that its seeds contain >50% of soluble carbohydrates.…”
Section: Discussionsupporting
confidence: 60%
“…A simple explanation for the strong preference for Indian ricegrass exhibited by kangaroo rats in this and numerous other studies (Kelrick and MacMahon ; Longland et al. ; Veech ) is that its seeds contain >50% of soluble carbohydrates.…”
Section: Discussionsupporting
confidence: 60%
“…). Soluble carbohydrates are thought to predict the relative preference of seeds in sagebrush communities (see Kelrick & MacMahon ; Kelrick et al . ) because they are a water‐efficient energy source and their relative percentage is a good measure of available digestible energy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that granivore preferences were correlated with assimilation efficiency (Soholt 1973, Whitford 1978, Withers 1982, Price 1983). In fact, at the Intermountain Great Basin (Kelrick and MacMahon 1985, Kelrick et al 1986) 7 different native seeds were offered to rodents, ants, and birds, and granivore preferences was correlated to the concentration of soluble carbohydrates and water in the seeds. Our results on cellulose, lignin, and ashes showed that Mulinum values were similar to the least preferred seed at Kelrick et al's study ( Artemisia tridentata ) and Phalaris to the most preferred seed ( Purshia tridentata ).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of seed removal and the relative importance of each granivore group vary among arid regions (Mares and Rosenzweig 1978, Morton 1985, Kerley 1991, Kelt et al 1996, Lopez de Casenave et al 1998) and several reasons may account for these differences. In arid environments, seeds vary in size, shape, presence of projections, thickness of the coat, chemical composition, amount and timing of dissemination (Kelrick and MacMahon 1985, Brown and Ojeda 1987), and granivores vary in their ability to handle different seeds (Pulliam and Brand 1975, Price and Brown 1983). Environmental, historical, and biogeographical factors may also determine the differences in granivory found across arid and semi‐arid regions of the world (Mares and Rosenzweig 1978, Mares 1993, Kelt et al 1996, Folgarait et al 1998).…”
mentioning
confidence: 99%